2006
DOI: 10.1207/s15327043hup1903_3
|View full text |Cite
|
Sign up to set email alerts
|

Applicant and Method Factors Related to Ethnic Score Differences in Personnel Selection: A Study at the Dutch Police

Abstract: The aim of this study was to examine applicant and method factors related to ethnic score differences on a cognitive ability test, a personality test, an assessment center (AC), an employment interview, and a final employment recommendation in the context of police officer selection (N = 13,526). Score differences between the majority group and the first-generation minority groups were comparable to research findings from the literature. However, score differences between the majority group and second-generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
13

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 51 publications
1
19
0
13
Order By: Relevance
“…Since the successful completion of Grade 12 is a prerequisite for becoming a South African Police Service member, the assumption is that English language competence levels have already been assessed. Furthermore, in a study investigating the relationship between language proficiency and results on a personality test in personnel selection, Dutch police applicants including six different ethnic groups had a standardized path coefficient between the variables of just .08 (De Meijer, Born, Terlouw, & van der Molen, 2006). These arguments suggest that the results relating to a possible bias because of subjectively reported difficulties with English language should not be overinterpreted.…”
Section: Discussionmentioning
confidence: 99%
“…Since the successful completion of Grade 12 is a prerequisite for becoming a South African Police Service member, the assumption is that English language competence levels have already been assessed. Furthermore, in a study investigating the relationship between language proficiency and results on a personality test in personnel selection, Dutch police applicants including six different ethnic groups had a standardized path coefficient between the variables of just .08 (De Meijer, Born, Terlouw, & van der Molen, 2006). These arguments suggest that the results relating to a possible bias because of subjectively reported difficulties with English language should not be overinterpreted.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the extent of GMA saturation in test content, generational status also influences immigrant test scores. de Meijer et al () found larger differences in favor of non‐immigrants with first‐generation immigrants and smaller differences with second‐generation applicants. Similarly, a meta‐analysis by te Nijenhuis et al () found immigrant and non‐immigrant groups differed by between one‐half and one full standard deviation, depending on the verbal and g saturation of the subtest, the immigrant group compared to, and the length of stay in the country (e.g., second‐generation immigrants generally score higher than first‐generation immigrants).…”
Section: Introductionmentioning
confidence: 98%
“…Despite the growth in immigration and the potential value of understanding the contribution of immigrant research on adverse impact, few studies have researched these groups and GMA testing. The majority of research comparing immigrant and non‐immigrant scores on GMA tests has been conducted in the Netherlands (de Meijer, Born, Terlouw, & van der Molen, ; te Nijenhuis & van der Flier, ). Cognitive subtests that strongly measure general intelligence show large mean differences between immigrants and majority members; subtests that less strongly measure general intelligence show smaller mean differences (te Nijenhuis & van der Flier, ; te Nijenhuis, Willigers, Dragt, & van der Flier, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a large number of empirical studies indicate that selection instruments show no cultural bias, they also point at the existence of language bias in subtests of IQ batteries with a substantial language component, and in scales of personality questionnaires that use difficult words or expressions that immigrants are unfamiliar with (e.g., te Nijenhuis & van der Flier, ; te Nijenhuis et al, ; van Leest, ). Other studies suggest that selection instruments contain both cultural bias and language bias against immigrants (de Meijer, Born, Terlouw, & van der Molen, ; Helms‐Lorenz, van de Vijver, & Poortinga, ; Wicherts & Dolan, ). So there appears a general agreement among researchers that language bias plays a role in selection instruments, although there is a disagreement about the size of the effect.…”
Section: Introductionmentioning
confidence: 99%